Long Noncoding RNA SNHG7 Is a Diagnostic and Prognostic Marker for Colon Adenocarcinoma - Jiang, Chengwei; Qu, Shanshan; Liu, Tie; Hao, Miao (Frontiers in Oncology, 2022)
Numerous studies have shown that long noncoding RNAs (lncRNAs) play a critical role in the malignant progression of cancer. However, the potential involvement of lncRNAs in colon adenocarcinoma (COAD) remains unexplored. In this study, the expression of lncRNA SNHG7 in colon cancer tissues and its correlation with clinical characteristics were analyzed based on data from The Cancer Genome Atlas (TCGA) database. SNHG7 was found to be highly expressed in 17 types of cancer, including COAD. Next, TCGA data were further investigated to identify differentially expressed genes, and Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses were performed. In addition, the relationship between SNHG7 expression and clinical features were analyzed. SNHG7 expression was found to be a potentially valuable indicator for COAD diagnosis and prognosis. Finally, gene set enrichment analysis showed that SNHG7 may affect lupus erythematosus and reactome cellular senescence, possibly influencing the prognosis of patients with COAD. Altogether, these results suggest that SNHG7 may be associated with the occurrence and development of COAD, having potential diagnostic and prognostic value.